2020
DOI: 10.3389/fimmu.2020.00323
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk Between Hippo-YAP Pathway and Innate Immunity

Abstract: Recognition of pathogen-associated molecular patterns (PAMPs) triggers expression of antiviral interferons and proinflammatory cytokines, which functions as the frontier of host defense against microbial pathogen invasion. Hippo-YAP pathway regulates cell proliferation, survival, differentiation and is involved in diverse life processes, including tissue homeostasis and tumor suppression. Emerging discoveries elucidated that the components of Hippo-YAP pathway, such as MST1/2, NDR1/2, and YAP/TAZ played crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 132 publications
(155 reference statements)
5
72
0
Order By: Relevance
“…The mammalian core kinases of the Hippo pathway comprise MST1/2 (ortholog of Drosophila Hippo/Hpo) 10 , SAV1 (also called WW45, salvador ortholog), LATS1/2 (Warts/Wts ortholog) 11 , 12 , and MOB1A/B (Mats ortholog) 13 . In addition, NDR1/2 (Trc ortholog) 14 and MAP4K (Happyhour/Hppy ortholog) 15 have been recently identified as novel components of the Hippo pathway 14 . The transcriptional co-activators YAP (also known as YAP1, Yorkie/Yki ortholog) 16 and TAZ (YAP paralog in mammals) 17 are the primary downstream effectors of the Hippo pathway 18 .…”
Section: The Hippo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian core kinases of the Hippo pathway comprise MST1/2 (ortholog of Drosophila Hippo/Hpo) 10 , SAV1 (also called WW45, salvador ortholog), LATS1/2 (Warts/Wts ortholog) 11 , 12 , and MOB1A/B (Mats ortholog) 13 . In addition, NDR1/2 (Trc ortholog) 14 and MAP4K (Happyhour/Hppy ortholog) 15 have been recently identified as novel components of the Hippo pathway 14 . The transcriptional co-activators YAP (also known as YAP1, Yorkie/Yki ortholog) 16 and TAZ (YAP paralog in mammals) 17 are the primary downstream effectors of the Hippo pathway 18 .…”
Section: The Hippo Pathwaymentioning
confidence: 99%
“…Increasing research in recent years has indicated an interplay between the Hippo and other pathways in intestinal regeneration, including the WNT 43 and Notch 44 pathway. Furthermore, the Hippo pathway has been suggested to be associated with inflammation, including the NF-κB pathways 45 , 46 and other components 9 , 47 , and also with immune-regulating pathways 15 .…”
Section: The Hippo Pathwaymentioning
confidence: 99%
“…Inflammatory cytokines in the TME activate YAP/TAZ and sustain angiogenesis ( 334 338 ). Inflammatory cytokines activate AP-1 ( 339 ), which promotes oncogenic growth in conjunction with YAP/TAZ ( 171 ).…”
Section: Yap/taz Sustain Tumor Angiogenesis Through Feedback Mechanismentioning
confidence: 99%
“…For example, YAP was found to cooperate with TEA domain transcriptional factor (TEAD) and activate forkhead box D1 (FOXD1) expression, thus alleviating chondrocyte senescence and OA [129]. In a murine OA model, YAP activation by transgenic overexpression or deletion of the upstream inhibitory kinase Mst1/2 binding sites preserves articular cartilage integrity, whereas downregulation of YAP by inflammatory cytokines through TAK1-mediated phosphorylation promotes cartilage disruption [130,131]. Furthermore, YAP directly interacts with TAK1 and NF-κB signaling by inhibiting substrate TAK1 accessibility and reducing NF-κB-induced matrix-degrading enzyme expression and cartilage degradation during OA pathogenesis [130].…”
Section: Hippo Pathway-yap/taz Signalingmentioning
confidence: 99%